Swinging the Maelstrom : A Critical Edition - Lowry, Malcolm, 1909-1957 (Book collections on Project MUSE., 2013)
Swinging the Maelstrom is the story of a musician enduring existence in the Bellevue psychiatric hospital in New York. Written during his happiest and most fruitful years, this novella reveals the deep healing influence that the idyllic retreat at Dollarton had on Lowry. This long-overdue scholarly edition will allow scholars to engage in a genetic study of the text and reconstruct, step by step, the creative process that developed from a rather pessimistic and misanthropic vision of the world as a madhouse (The Last Address, 1936), via the apocalyptic metaphors of a world on the brink of Armageddon (The Last Address, 1939), to a world that, in spite of all its troubles, leaves room for self-irony and humanistic concern (Swinging the Maelstrom,1942- 944).